Physical Literacy Awareness: The Effect on Increasing Students' Abdominal Muscle Endurance in Wetland Environments - Mashud, M (Universitas Pendidikan Indonesia, 2024)
Physical Literacy awareness is a key aspect in understanding and improving students' physical health and fitness. This study investigated the impact of Physical Literacy Awareness in improving students' abdominal muscular endurance in a wetland environment. The study explored how a program focusing on physical literacy, when implemented in a wetland environment, impacted students' abdominal muscular endurance. The research method uses an equivalent time series, namely an experimental method applying a time series design. This method is carried out by carrying out three tests, namely an initial test followed by treatment. The second test continues with the treatment and ends with the third test. The research population as well as the research sample was 133 students. The data analysis technique uses the non-parametric Kruskal-Wallis test because the data is not normally distributed. Based on the Kruskal-Wallis Test data analysis technique, it shows a significance value of 0.015 0.05, so there is a significant difference. The results can be said that there is a significant difference between test-1, test-2 and test-3 in students. Based on the results of the study, it can be concluded that physical literacy awareness can increase physical literacy awareness. increase the abdominal muscle strength of students in wetland areas. This study provides valuable insights into the role of Physical Literacy Awareness in improving college students' abdominal muscle endurance. The findings showed that the implementation of the physical literacy awareness program had a significant positive influence on improving abdominal muscle endurance in a wetland environment.